PENGUATAN KAPASITAS UMKM LUWAK COFFEE LOKASARI MELALUI TEKNOLOGI TEPAT GUNA DAN TATA KELOLA BERKELANJUTAN - Sudana, I Ketut; Arta, I Kadek Juni; Sumaryani, N Putri (Universitas Mataram, 2025)
The challenges faced by the Luwak Coffee Lokasari Farmers Group (UMKM) in Karangasem Regency, Bali, include traditional civet coffee processing, a lack of understanding of business management, and suboptimal digital marketing. The objective of the program was to improve production efficiency, management quality, and market access. The program employed a participatory empowerment approach, consisting of socialization, training in appropriate technology and business governance, implementation assistance, and evaluation and reflection. The training covered simple fermentation technology, environmentally friendly drying equipment, digital financial management, stock management, and branding strategies. The results showed significant improvements: coffee production increased from 4 kg to 12 kg per month, financial literacy increased from 20% to 85%, technology utilization increased from 0% to 90%, and digital market access increased from 5% to 80%. Tourist visits also increased by 400%. This program successfully increased production capacity, sustainable management, and digital marketing. Interventions based on appropriate technology, managerial strategies, and digital transformation have proven effective in supporting the independence and sustainability of locally-based MSMEs.